Antitumor activity of RT2 peptide derived from crocodile leukocyte peptide on human colon cancer xenografts in nude mice - Maraming, Pornsuda; Klaynongsruang, Sompong; Boonsiri, Patcharee; Maijaroen, Surachai; Daduang, Sakda; Chung, Jing‐Gung; Daduang, Jureerut (Environmental toxicology, 2018)
RT2, derived from the leukocyte peptide of Crocodylus siamensis, can kill human cervical cancer cells via apoptosis induction, but no evidence has shown in vivo. In this study, we investigated the antitumor effect of RT2 on human colon cancer xenografts in nude mice. Twenty‐four mice were injected subcutaneously with human colon cancer HCT 116 cells. Eleven days after cancer cell implantation, the mice were treated with intratumoral injections of phosphate buffered saline (PBS) or RT2 (0.01, 0.1, and 1 mg/mouse) once every 2 days for a total of 5 times. The effect of a 10‐day intratumoral injection of RT2 on body weight, biochemical, and hematological parameters in BALB/c mice showed no significant difference between the groups. Tumor volume showed a significant decrease only in the treatment group with RT2 (1 mg/mouse) at day 6 (P < .05), day 8 (P < .01), and day 10 (P < .01) after the first treatment. The protein expression levels of cleaved poly (ADP‐ribose) polymerase (PARP), apoptosis‐inducing factor (AIF), and the p53 tumor suppressor protein (p53) in xenograft tumors increased after treatment with RT2 (1 mg/mouse) compared to those in the PBS‐injected group. Moreover, RT2 increased the expression of Endo G and Bcl‐2 family proteins. Therefore, the peptide RT2 can inhibit tumor growth via the induction of apoptosis in an in vivo xenograft model.